2014
DOI: 10.3174/ajnr.a3926
|View full text |Cite
|
Sign up to set email alerts
|

Complex Hemodynamic Insult in Combination with Wall Degeneration at the Apex of an Arterial Bifurcation Contributes to Generation of Nascent Aneurysms in a Canine Model

Abstract: BACKGROUND AND PURPOSE:The detailed mechanisms of cerebral aneurysm generation remain unclear. Our aim was to investigate whether specific hemodynamic insult in combination with arterial wall degeneration leads to the development of aneurysms in a canine model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…In canine models, disruption of internal elastic lamina, loss of medial smooth-muscle cells, reduced proliferation of smooth-muscle cells, and loss of fibronectin were observed at the regions with higher WSS than at the normal physiological levels [ 27 ]. Other studies also claimed that WSS higher than the normal physiologic level may disrupt the normal function of endothelial cells [ 28 29 ]. Therefore, increased WSS may impede neointimal formation which is induced by coil placement.…”
Section: Discussionmentioning
confidence: 99%
“…In canine models, disruption of internal elastic lamina, loss of medial smooth-muscle cells, reduced proliferation of smooth-muscle cells, and loss of fibronectin were observed at the regions with higher WSS than at the normal physiological levels [ 27 ]. Other studies also claimed that WSS higher than the normal physiologic level may disrupt the normal function of endothelial cells [ 28 29 ]. Therefore, increased WSS may impede neointimal formation which is induced by coil placement.…”
Section: Discussionmentioning
confidence: 99%
“…When blood flow enters an arterial bifurcation, it exhibits complex hemodynamic features, some of which may correlate with aneurysm formation. 2,5,15,16 In this study, we analyzed a series of MCA bifurcations with and without aneurysms and explored the hemodynamic factors involved in aneurysm development. We found that MCA aneurysms were commonly located on the inclined MCA bifurcations, consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…[ 128 ] 2014 X Surgical Rabbits Saccular and fusiform X Donzelli R. [ 129 ] 2014 X Surgical Rabbits Saccular X Erhardt S. [ 130 ] 2014 X Surgical Rabbits Saccular X Cebral J.R. [ 131 ] 2014 X Surgical Rabbits Saccular X X Wang J. [ 132 ] 2014 X Endogenous Dogs Saccular X ...…”
Section: Methodsmentioning
confidence: 99%